Maintaining the quality of rainbow trout (Oncorhynchus mykiss) fillets by treatment of red onion peel extract during refrigerated storage: Assessment of onion peel extract in fish quality - Uçak, Ilknur; Khalily, Rowida; Abuibaid, Ahlam K.M.; Abidemi Ogunkalu, Oluwatosin (Progress in Nutrition, 2018)
Due to excessive onion wastes are produced in the food industry, possible ways of their utilization are need to be searched. Considering the consumers concerns about the synthetic ingredients, onion peels can be assessed as a natural source in foods. In this study, onion peel extract (OPE) was evaluated as natural antioxidant and antimicrobial agent in prolonging the shelf life of rainbow trout fillets. The fish fillets were treated with 5 and 10% OPE. One batch was left as control without extract. Peroxide value (PV), thiobarbituric acid (TBARS), para-anisidine value (p-Av), total mesophilic aerobic and total psychrophilic aerobic bacteria, Enterobacteriaceae count, and sensory quality of fillets were evaluated during 14 days of storage. OPE was able to delay lipid oxidation compared to control, since the scores of PV, TBARS and p-Av of the fillets treated with OPE showed lower levels. With the increase of OPE concentration, successful results were observed in the growth of bacteria and the lowest bacterial numbers were obtained from 10% OPE treated group. Shelf-life of fish was found as 6, 12 and 14 days for the control, 5% OPE and 10% OPE treated groups, respectively. The results revealed that OPE contributed to maintain the oxidative, microbiological and sensory quality of rainbow trout fillets during storage. Additionally, finding of this research could help to evaluation of food wastes and the industrial usage of these products as a natural preservative.